#TITLE_ALTERNATIVE# - ISNAENDA IKHSAN NIM: 10311012, MUHAMMAD
Star cluster is a star system consisting of a group of stars that stay in one place, gravitationally bound, and evolving together. Studying evolution of star cluster become one of important aspect to understanding about star evolution. Binary star is one of important factor that affect star cluster evolution. To understand more about star cluster evolution, in this study will be made a two-body simulation that sepecifically simulating an interaction that happen between binary star. To get a good result we use a regularization method, Kustaanheimo-Stiefel Regularization, which is specifically solving problem about close encounter problem between two-body. The idea of this regularization method is transforming the coordinates and using varying timestep. The binary star coordinat will be transfromed from Cartesian to KS coordinat system, so when the system face an extreme condition, such as the distance between star close to zero, our calculation will still give a good result with minimalizing the error. Using regularization will make the timestep per integration that we use adapting the binary star condition, so the integration will be more efficient. Based on the result that we get from simulation, we can make a conclusion that the regularization method that we use is good enough to simulate binary star with the error of the parameter is small. This method is also stable enough to simulating binary star even there is a third-body added to perturbing the system. The process of choosing timestep by this method is showing a good result too, showed by the relation between the value of timestep and distance of binary star.